Marketing Mix Strategy in Increasing Customer Loyalty CV. Elmira Productions - Muh. Shadri Kahar Muang; Muzayyanah Jabani; Muhammad Hidayatur Rahman (Dinamis : Journal of Islamic Management and Bussiness, 2022)
This study discusses how the Marketing Mix Strategy in Increasing Customer Loyalty at CV. Elmira Productions. This study aims to determine the marketing strategy implemented by CV Elmira Production through marketing mix and SWOT analysis in increasing consumer loyalty. The subject of this research is the owner of CV Elmira Production. Data collection techniques carried out by researchers were interviews and documentation directly to the business owner. Besides that, there is additional data from reading books and also other sources related to the research title. The data obtained from the results of data collection are then analyzed using SWOT analysis to find out what are the Strengths, Weaknesses, Opportunities, as well as threats from the marketing strategy undertaken by the company. In addition, the results of the SWOT analysis research are shown by the Cartesian diagram calculation results that CV. Elmira Production is in quadrant I, which is aggressive with the implementation of a Growth Oriented Strategy which is a very profitable situation for the company. Where, the company has the power so that it can take advantage of existing opportunities.